2018
DOI: 10.1128/msphere.00249-18
|View full text |Cite|
|
Sign up to set email alerts
|

Asymptomatic Shedding of Respiratory Virus among an Ambulatory Population across Seasons

Abstract: Respiratory viruses are common in human populations, causing significant levels of morbidity. Understanding the distribution of these viruses is critical for designing control methods. However, most data available are from medical records and thus predominantly represent symptomatic infections. Estimates for asymptomatic prevalence are sparse and span a broad range. In this study, we aimed to measure more precisely the proportion of infections that are asymptomatic in a general, ambulatory adult population. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 21 publications
3
46
1
1
Order By: Relevance
“…Conversely, the impact of these infectious agents on healthy adults and the role of asymptomatic infections on transmission dynamics have not been properly investigated. A recent study found high levels of asymptomatic respiratory infection among an ambulatory adult population in New York City …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the impact of these infectious agents on healthy adults and the role of asymptomatic infections on transmission dynamics have not been properly investigated. A recent study found high levels of asymptomatic respiratory infection among an ambulatory adult population in New York City …”
Section: Discussionmentioning
confidence: 99%
“…IAVs and IBVs were detected at higher frequencies than other respiratory viruses. A recent study that collected nasopharyngeal swabs of 2685 tourists in New York City reported a higher detection frequency for HRV and HCoV than IAV at 3.2%, 2.4%, and 0.2%, respectively [6,7]. To attain a comprehensive understanding on the potential transmission modes for respiratory viruses, future studies should sample concurrently from humans and their surrounding environment.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial global disease burden is attributed to influenza virus and respiratory syncytial virus (RSV), which cause lower respiratory infections and cardiopulmonary complications [1][2][3][4]. While most infections are associated with acute respiratory illnesses, respiratory viruses can also infect without causing symptoms [5][6][7], although the infectivity of asymptomatic cases is uncertain. A common feature of respiratory viruses is their ability to spread via multiple non-mutually exclusive modes, by direct contact or indirectly via large droplets, fine droplet nuclei, or fomites [8][9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ces technologies qui augmentent considérablement notre éventail de données microbiologiques suscitent beaucoup d'interrogations sur la physiopathologie des maladies infectieuses en particuliers sur la notion d'infection asymptomatique et de rôle pathogène ou l'importance clinique des coinfections. La fréquence de détection d'agents pathogènes respiratoires chez les patients asymptomatiques varie avec l'âge, (20-50 % chez l'enfant et 2-50 % chez l'adulte selon les études), le nombre d'enfants vivant au foyer familial ou l'agent pathogène en cause (plus de cas symptomatiques avec le virus de la grippe, VRS, hMPV) [13][14][15][16][17][18]. De même, les patients immunodéprimés peuvent avoir une excrétion prolongée de microorganismes ou d'acides nucléiques non infectieux détectés par PCR sans nécessairement avoir de symptômes cliniques associés.…”
Section: Contreunclassified